Exploring the critical factors influencing online lending intentions - Peng Wang (Financial Innovation, 2015)
Background: Online lending (P2P lending) is a type of internet finance mainly used to meet the financial needs of small and medium-sized enterprises and groups of individuals. It is a supplement to the traditional financial system. Method: This paper uses PPDai.com - the most influential online lending platform in China - as a research object to study the leading factors that affect lenders' loan trust and perception of information asymmetry. It also studies the impacts of these factors on lending intention. Results: The results of this study show that the lending intention is mainly influenced by trust; perceived information asymmetry will affect trust, but it will not have a direct impact on lending intention. Trust is significantly affected by the borrowers' reputation and information integrity. Information asymmetry has various causes, including structural assurance and legitimacy. This perception of information asymmetry significantly prevents the further development of online P2P lending. Conclusion: The findings in this research imply that there are profound differences between online lending and online purchasing, thus the results obtained in the traditional e-commerce market cannot be applied in the field of online lending without verification.
Keywords: 650; Internet investment; Internet finance; Trust